Physical Education in evening classes in the public school system in the municipality of MARINGÁ, State of PARANÁ, BRAZIL - Amauri Aparecido Bassoli de Oliveira; Gislaine Lisboa (Revista da Educação Física)
The aim of this descriptive investigation was to analyze the state of art of physical education in evening classes of public schools in Maringá. Seventeen (71%) of the teachers acting in evening classes of 13 (76%) public schools that offer physical education in their evening classes were interviewed. A semi-structured interview with indicators comprising personal aspects and practice in every day teaching was applied. The data indicate that the teachers have specialization courses or master’s degrees, but their teaching practice is out of time and further studies are necessary to make them overcome current teaching problems and make teaching more effective and useful for all participants.